STOKES PHENOMENON AND MATCHED ASYMPTOTIC EXPANSIONS - Olde Daalhuis, A; Chapman, S; King, J; Ockendon, J; Tew, R (1995)
This paper describes the use of matched asymptotic expansions to illuminate the description of functions exhibiting Stokes phenomenon. In particular the approach highlights the way in which the local structure and the possibility of finding Stokes multipliers explicitly depend on the behaviour of the coefficients of the relevant asymptotic expansions.